Respuesta :

Answer:

D) 9

Step-by-step explanation:

[tex]3 - (-3) + 7 - 4 =\\\mathrm{Follow\:the\:PEMDAS\:order\:of\:operations}\\\\\mathrm{Add\:and\:subtract\:\left(left\:to\:right\right)}\:\:\\\\\mathrm{Apply\:rule\:}-\left(-a\right)\:=\:+a\\\\-\left(-3\right)=+3\\\\=3+3+7-4\\\\3+3=6\\\\=6+7-4\\\\6+7=13\\\\=13-4\\\\13-4\\=9[/tex]

Ver imagen ZJSG09112007
THE ANSWER: D) 9

Explanation: If you have two negative signs together you will turn that into a addition sign. So three plus three is 6. Then you will add 7 to six which is 13! Finally you would subtract 4 which will give you your final answer 9.